Advanced MR Imaging of the Human Nucleus Accumbens—Additional Guiding Tool for Deep Brain Stimulation. Issue 5 (16th April 2015) - Lucas‐Neto, Lia; Reimão, Sofia; Oliveira, Edson; Rainha‐Campos, Alexandre; Sousa, João; Nunes, Rita G.; Gonçalves‐Ferreira, António; Campos, Jorge G.
<x xml:space="preserve">Abstract</x> Objective The human nucleus accumbens (Acc) has become a target for deep brain stimulation (DBS) in some neuropsychiatric disorders. Nonetheless, even with the most recent advances in neuroimaging it remains difficult to accurately delineate the Acc and closely related subcortical structures, by conventional MRI sequences. It is our purpose to perform a MRI study of the human Acc and to determine whether there are reliable anatomical landmarks that enable the precise location and identification of the nucleus and its core/shell division. Methods For the Acc identification and delineation, based on anatomical landmarks, T1WI, T1IR and STIR 3T‐MR images were acquired in 10 healthy volunteers. Additionally, 32‐direction DTI was obtained for Acc segmentation. Seed masks for the Acc were generated with FreeSurfer and probabilistic tractography was performed using FSL. The probability of connectivity between the seed voxels and distinct brain areas was determined and subjected to k‐means clustering analysis, defining 2 different regions. Results With conventional T1WI, the Acc borders are better defined through its surrounding anatomical structures. The DTI color‐coded vector maps and IR sequences add further detail in the Acc identification and delineation. Additionally, using probabilistic tractography it is possible to segment the Acc into a core and shell division and establish its structural connectivity with different brain areas. Conclusions Advanced MRI techniques allow in vivo delineation and segmentation of the human Acc and represent an additional guiding tool in the precise and safe target definition for DBS.